452 Dermal Filler Injection Leading to Facial Cellulitis: A Case Report. (12th October 2021) - Baldock, E; Devine, C; Holden, A; Colbert, S
Abstract: Background: Aesthetic medicine is a rapidly expanding field that is progressively becoming a normal part of society's health and beauty regime. Hyaluronic Acid dermal filler injections are the second most widely performed aesthetic procedure, following Botulinum Toxin type A. Although serious complications are rare, they can have a detrimental impact on aesthetic outcome and general health. Infections following dermal fillers can be difficult to treat and have the potential to require hospital admission, intravenous antibiotics and surgical intervention. Case description: We present a case of a 41-year-old female who suffered from facial cellulitis as a consequence of palpebro-malar groove dermal filler injections. The patient had 0.1ml of Monalisa dermal filler injected over her right malar prominence and suffered complications 6 days later, which eventually lead to the need for hospital admission on day 12 following the procedure for intravenous antibiotics. The management of this aesthetic procedure complication is outlined to highlight the risks and serious complications of these procedures. Conclusions: Facial cellulitis is a rare adverse event following facial filler injection; however, it is an important risk factor to discuss during the consent process for these procedures. In addition, it is important that a highly trained and skilled professional performs these injections using a sterile non-touch technique due to the potential for serious complications and the anatomical proximity to vital structures.